Information and communication technologies in Biology education: Theoretical approaches (Research, Society and Development, 2021)
Given the importance of integrating Information and Communication Technologies (ICT) in a Biology teaching context, the present study aimed to characterize the main digital technologies and trends in theoretical frameworks (theoretical foundation and literature review) of studies that investigate the use of technologies in education, emphasizing the teaching of science and biology. In it, we present a reflection of a set of studies, during which digital technologies have assumed a growing presence within the classroom in basic education. The bibliographic review consisted mainly of books, scientific articles, theses and dissertations, especially copies available online on research platforms such as Scielo, CAPES and Google Scholar. The main descriptors used were: technologies in education, science and biology teaching, science education, ICT, basic education. The research showed that it is essential to discuss the approaches needed to enable the process of induction and constant innovation in education and learning. Achieving the goal of meaningful integration of technology in the classroom, does not depend only on factors related to technology, the personal pedagogical beliefs of teachers play a fundamental role in their pedagogical decisions on how to integrate technology in their classroom practices. The great challenge is to find positive and viable ways of integrating ICTs in the teaching-learning process, within the framework of the current curricula, the professional situation of teachers and the concrete conditions of performance in each school.